1991
DOI: 10.1063/1.349790
|View full text |Cite
|
Sign up to set email alerts
|

Stress in polyimide films having a rodlike molecular skeleton formed on a silicon substrate

Abstract: Stress measurements of polyimide films deposited on silicon wafers were performed in situ during the curing and cooling cycles. The films were constructed from a single polyimide having a rodlike molecular skeleton. The stress in the film varied with film thickness. The stress before curing decreased with increasing film thickness. On the other hand, the stress after the thermal cycle increased with increasing film thickness, resulting from the increasing thermal coefficient of expansion. This phenomenon was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…They also showed that the presence of a metal frame which supports PAA films during imidization (bifix-cure) lowers the TEC of the resulting PI films and inferred that the decreased TEC results from an enhanced molecular orientation. Numerous papers described that the TEC mismatch between a substrate such as Cu and the PI film is responsible for delamination at the interface and cracking in the PI film. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also showed that the presence of a metal frame which supports PAA films during imidization (bifix-cure) lowers the TEC of the resulting PI films and inferred that the decreased TEC results from an enhanced molecular orientation. Numerous papers described that the TEC mismatch between a substrate such as Cu and the PI film is responsible for delamination at the interface and cracking in the PI film. , …”
Section: Introductionmentioning
confidence: 99%
“…Numerous papers described that the TEC mismatch between a substrate such as Cu and the PI film is responsible for delamination at the interface and cracking in the PI film. 3,[5][6][7][8][9][10] Recently, a high-temperature annealing method in which aromatic PI films were used as a precursor was developed to obtain a highly crystalline graphite applicable as a monochromator for X-ray analysis. In this method, the high-temperature annealing of PI films cured in a frame provided highly crystalline graphite, whereas that of the films cured free-standing did not.…”
Section: Introductionmentioning
confidence: 99%
“…As oxidation temperature increases, the film density increases giving rise to increase in the adhesion and decreasing the stress. The decrease in stress with increase in temperature is reported by Nomura et al [19] and Kinbara et al [20]. As substrate temperature increases, mobility of adatoms increases and also elimination of trapped excess vacancies occurs which results in increase in adhesion.…”
Section: Discussionmentioning
confidence: 74%